Design Thinking Learning with a Neuro-Linguistic Programming (NLP) Approach to Enhance Autonomous Learning in Early Writing and Reading - Kristiantari, Maria Goreti Rini; Purnami, I Gusti Ayu Lokita; Tristiantari, Ni Ketut Desia; Bayu, Gede Wira; Dewantara, Kadek Andre Karisma; Dewi, Ni Putu Utami (International Journal of Language Education, 2025)
The purpose of this study is to develop learning model of design thinking learning with a Neuro-Linguistic Programming (NLP) approach to enhance autonomous learning in early writing and reading. This study conducted base on problems that exist in strategies for teaching early writing and reading in elementary schools and seek solutions that can increase the effectiveness of this process. This study adopts a design-based research approach utilizing the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis in this study will employ both qualitative and quantitative methods. The findings of this study indicate a significant improvement in early writing and reading after using design thinking learning with a Neuro-Linguistic Programming (NLP) approach. The Design Thinking approach integrated with NLP provides a comprehensive solution to improve reading, writing and autonomous learning skills. By implementing the stages of Design Thinking equipped with NLP principles, students can be actively involved in the learning process, develop basic literacy skills, and build a more independent, confident, and disciplined learning attitude. The learning concept that integrates Design Thinking and Neuro-Linguistic Programming (NLP) offers an innovative and effective approach to improving early reading and writing skills as well as autonomous learning.